Fe / NiMo-IF catalyst and preparation method and application thereof

By preparing the Fe/NiMo@IF catalyst on a foamed iron substrate, the problem of poor performance of NiFe-based catalysts in electrocatalytic water decomposition and analytical hydrogen reaction was solved, and efficient electrocatalytic water decomposition performance was achieved, and the stability of the catalyst was significantly improved.

CN119753746APending Publication Date: 2025-04-04GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411987435.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

Smart Images

  • Figure CN119753746A_ABST
    Figure CN119753746A_ABST
Patent Text Reader

Abstract

The invention provides a Fe / NiMo-IF catalyst and a preparation method and application thereof.The preparation method comprises the following steps that SO1, nickel salt, molybdenum salt and a precipitant are added into a mixed solvent and stirred until the nickel salt, the molybdenum salt and the precipitant are dissolved, and a mixed solution is obtained; the molar ratio of the nickel salt to the molybdenum salt to the precipitating agent is (1.9 to 14.0): (1.3 to 2.3): 100; the preparation method comprises the following steps: preparing a mixed solution, namely SO2, vertically immersing a foam iron substrate into the mixed solution in the step SO1, reacting for 3-18 hours at the temperature of 80-180 DEG C, naturally cooling to room temperature after the reaction is completed to obtain a substrate on which a catalyst grows, cleaning the surface of the substrate, and drying to obtain the Fe / NiMo-IF catalyst. The invention also provides application of the catalyst in electrochemical water decomposition. The preparation method disclosed by the invention is simple, good in controllability, short in time consumption and easy for batch production; and the prepared catalyst is uniform in morphology distribution, good in conductivity and relatively good in thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic materials, and in particular to a Fe / NiMo@IF catalyst and a preparation method and application thereof. Background Art

[0002] Energy is the foundation of human society and economic development, and new energy technology is the inevitable way to solve the sustainable development of energy. Hydrogen is a green energy with the advantages of high energy density, no pollution, and renewable. From a long-term perspective, using renewable energy to electrolyze water to produce hydrogen is the best way to provide sufficient clean hydrogen energy.

[0003] Electrocatalytic water splitting (WE) is a green and sustainable hydrogen production technology that is easily combined with other renewable energy sources such as solar energy, tidal energy, and wind energy, and has attracted much attention. Designing low-cost, easy-to-prepare, high-efficiency, and high-stability bifunctional electrocatalysts is a key condition for promoting the development of the hydrogen energy economy.

[0004] At present, precious metal catalysts such as Pt, Pd, and Ir are the best hydrogen evolution catalysts for electrocatalytic water splitting. However, due to the low global reserves of precious metals and their high prices, their large-scale commercial applications are limited. Therefore, it is of great significance to develop non-precious metals such as transition metals (such as Ni, Co, Fe, and Mo, etc.) based catalysts for electrocatalytic water splitting. Studies have shown that the performance of catalysts can be significantly enhanced by combining multiple metal elements. Compared with other catalysts (such as NiCo-based, NiFe-based, CoFe-based, etc.), NiFe-based catalysts have better catalytic performance in the oxygen evolution reaction (OER) in electrocatalytic water splitting. However, due to the insufficient adsorption capacity of such catalysts for H, their performance in the hydrogen evolution reaction (HER) is poor, which makes it difficult to meet the needs of practical applications. Summary of the invention

[0005] Based on this, the embodiment of the present invention provides a Fe / NiMo@IF catalyst and a preparation method and application thereof, aiming to solve the problem that the existing NiFe-based catalysts perform poorly in the hydrogen evolution reaction (HER) of electrocatalytic water decomposition and have insufficient adsorption capacity for H. The preparation method of the present application is simple to operate, highly controllable, time-saving, and easy to scale up. The prepared Fe / NiMo@IF catalyst has uniform morphology distribution, good electrical conductivity and excellent thermal stability, and has excellent performance in electrocatalytic water decomposition applications.

[0006] To achieve the above object, on the one hand, an embodiment of the present invention provides a method for preparing a Fe / NiMo@IF catalyst, comprising the following steps:

[0007] SO1, adding nickel salt, molybdenum salt and precipitant into a mixed solvent, stirring until dissolved, to obtain a mixed solution; the molar ratio of the nickel salt, the molybdenum salt and the precipitant is (1.9-14.0): (1.3-2.3): 100;

[0008] SO2, immerse the foamed iron substrate vertically in the mixed solution in step SO1, and then react at 80°C to 180°C for 3h to 18h. After the reaction is completed, naturally cool to room temperature to obtain a substrate with catalyst growth, clean the surface of the substrate, and dry it to obtain a Fe / NiMo@IF catalyst.

[0009] As a preferred embodiment, in step SO1,

[0010] The nickel salt is preferably Ni(NO3)2·6H2O or Ni(CH3COO)2·4H2O.

[0011] The molybdenum salt is preferably (NH4)6Mo7O 24 ·4H2O.

[0012] The precipitant is preferably thiourea. The mixed solvent is preferably a solvent in which ethylene glycol and deionized water are mixed in a volume ratio of (1-10):(1-10).

[0013] As a preferred embodiment, in step SO2,

[0014] The foam iron substrate is preferably pretreated in the following manner: soaking the foam iron substrate in acetone for 10 to 20 minutes, taking it out, and washing it with deionized water, then soaking the cleaned foam iron substrate in hydrochloric acid for 2 to 4 minutes, taking it out, and washing it with deionized water to obtain a pretreated foam iron substrate.

[0015] The cleaning is achieved by ultrasound, the number of ultrasounds is preferably 2 to 4 times, and the duration of each ultrasound is preferably 5 to 10 minutes.

[0016] The hydrochloric acid is preferably 0.1 mol / L hydrochloric acid.

[0017] The cleaning is preferably achieved by ultrasound, the number of ultrasounds is preferably 2 to 4 times, and the duration of each ultrasound is preferably 3 to 5 minutes.

[0018] The cleaning is preferably carried out by sequentially using deionized water and ethanol ultrasonically for multiple times.

[0019] The drying is preferably carried out at 60° C. for 12 hours.

[0020] On the other hand, an embodiment of the present invention also provides a Fe / NiMo@IF catalyst prepared by the above preparation method.

[0021] As a preferred embodiment, the Fe / NiMo@IF catalyst has a nanoscale heterogeneous structure, wherein the nanoscale heterogeneous structure refers to NiMoO4 vertically grown in an array in the form of nanorods on the surface of a foamed iron substrate, wherein the nanorods are intertwined to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

[0022] On the other hand, the embodiments of the present invention also provide applications of the Fe / NiMo@IF catalyst, and the Fe / NiMo@IF catalyst can be applied to electrocatalytic water decomposition.

[0023] As a preferred embodiment, the electrocatalytic water splitting is preferably alkaline electrocatalytic water splitting hydrogen or alkaline electrocatalytic water splitting oxygen. Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The present invention uses foamed iron as a substrate to construct a skeleton structure, and through a one-step hydrothermal reaction, a Fe / NiMo@IF catalyst with a nanoscale heterogeneous structure is prepared on the substrate of the skeleton structure. In the catalyst structure, NiMoO4 grows vertically on the surface of the foamed iron substrate in the form of an array of nanorods, and the nanorods are intertwined to form an open porous structure, and the surface and edge of the nanorods are loaded with Fe3O4 nanoparticles. The catalyst has uniform morphology distribution, good crystallinity, high thermal stability, and good electrical conductivity.

[0025] (2) The preparation method of the present invention has the characteristics of simple operation, strong controllability, short time consumption and easy large-scale production; the prepared catalyst only needs a low overpotential of 265mV to reach 100mA·cm in the electrocatalytic water-oxygen separation reaction. -2 In the electrocatalytic water decomposition hydrogen reaction, only 205mV low overpotential is required to reach 100mA·cm -2 ; at 100mA·cm -2 Under the current density condition, the Fe / NiMo@IF catalyst can continuously and stably carry out the electrocatalytic water-to-oxygen separation reaction for up to 200 hours, and its activity remains stable without obvious attenuation, showing good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 The Raman images of the Fe / NiMo@IF catalyst prepared in Example 1 of the present invention and the Fe3O4@IF of Comparative Example 1;

[0028] Figure 2 The scanning electron microscope images of the Fe / NiMo@IF catalyst prepared in Example 1 of the present invention and the Fe3O4@IF of Comparative Example 1;

[0029] Figure 3 HER performance diagram of the Fe / NiMo@IF catalyst prepared in Example 1 of the present invention and the Fe3O4@IF of Comparative Example 1;

[0030] Figure 4 It is an OER performance diagram of the Fe / NiMo@IF catalyst prepared in Example 1 of the present invention and the Fe3O4@IF of Comparative Example 1;

[0031] Figure 5 The Fe / NiMo@IF catalyst prepared in Example 1 of the present invention is -2 OER stability results diagram.

[0032] In the present application, the Fe / NiMo@IF catalyst is a Fe3O4 / NiMoO4@IF (can also be expressed as Fe3O4@NiMoO4 / IF) catalyst, wherein @IF represents the foamed iron substrate skeleton, and “ / ” and “@” play a spacing role and have no actual meaning.

[0033] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, top, bottom...), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0036] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0037] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.

[0038] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0039] In an embodiment of the present application, the foam iron substrate is preferably pretreated in the following manner: the foam iron substrate is soaked in acetone (to achieve the purpose of degreasing) for 10 minutes to 20 minutes, taken out, and washed with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid (which can produce divalent iron and trivalent iron on the iron substrate to ensure the formation of Fe3O4) for 2 minutes to 4 minutes, taken out, and washed again with deionized water (to wash away the hydrochloric acid residual on the surface to ensure the stability of the Fe / Ni@FF catalyst) to obtain a pretreated foam iron substrate.

[0040] By pretreating the foamed iron substrate, the iron element on the surface of the substrate can be guaranteed to exist in the form of divalent iron or trivalent iron to the greatest extent, which can well guarantee the yield of Fe3O4, and then guarantee the morphology of the Fe / NiMo@IF catalyst and make it evenly distributed. If the foamed iron substrate is not pretreated, the yield of Fe3O4 is very low, and the Fe / NiMo@IF catalyst with evenly distributed morphology cannot be obtained.

[0041] In the present application, the nickel salt is converted into nickel hydroxide by providing hydroxide ions through the precipitation agent thiourea, and the foamed iron substrate is converted into ferrosoferric oxide under high temperature hydrothermal conditions and in an alkaline environment provided by thiourea.

[0042] The present invention uses a foamed iron substrate as a skeleton structure and provides an iron source. By controlling the amount of each reactant and the reaction conditions, a one-step hydrothermal reaction is performed on the skeleton structure to prepare a heterogeneous Fe / NiMo@IF catalyst. The prepared catalyst only needs a low overpotential of 265mV to reach 100mA·cm in the electrocatalytic water desorption oxygen reaction. -2 In the electrocatalytic water decomposition hydrogen reaction, only 205mV low overpotential is required to reach 100mA·cm -2 ; at 100mA·cm -2 Under the current density condition, the Fe / NiMo@IF catalyst can continuously and stably carry out the electrocatalytic water-to-oxygen separation reaction for up to 200 hours, and its activity remains stable without obvious attenuation, showing good stability.

[0043] In the examples of the present application, the performance of the prepared Fe / NiMo@IF catalyst is greatly improved:

[0044] (1) Core-shell structure: The Fe3O4 layer as the shell provides good electronic conductivity and structural stability, while the NiMoO4 nanorods as the core provide abundant active sites in the catalytic reaction.

[0045] (2) The Fe / NiMo@IF catalyst is well aligned, and the core-shell nanorods can provide a large surface area, expose more active sites, and promote the rapid desorption of bubbles, thereby improving the catalytic performance.

[0046] (3) There is a strong interaction between Fe3O4 and NiMoO4, which leads to electron redistribution and produces more oxygen vacancies, which improves the adsorption capacity of H2O and oxygen-containing reaction intermediates, thereby accelerating the HER and OER reactions.

[0047] (4) The close interfacial contact between NiMoO4 and Fe3O4 can effectively promote the charge transfer during HER and OER, thereby improving the HER and OER activities of Fe / NiMo@IF catalysts.

[0048] (5) Synergistic effect: There is a good synergistic effect between Fe3O4 and NiMoO4, which makes the Fe / NiMo@IF catalyst show lower overpotential and higher stability in both HER and OER reactions, thus improving the overall catalytic performance.

[0049] In the examples of the present application, unless otherwise specified, the raw materials and reagents used in the examples of the present invention are all conventionally purchased raw materials and reagents, and all the reagents used are analytical grade reagents.

[0050] Example 1

[0051] A method for preparing a Fe / NiMo@IF catalyst comprises the following steps:

[0052] SO1, add 0.915mmol nickel salt, 0.108mmol molybdenum salt and 6.57mmol precipitant into 20mL mixed solvent, stir and dissolve to obtain a mixed solution;

[0053] SO2, immerse the foamed iron vertically into the mixed solution in step SO1, and then react at 140°C for 6 hours. After the reaction is completed, naturally cool to room temperature to obtain a substrate with the catalyst grown on it, clean the surface of the substrate, and dry it to obtain the Fe / NiMo@IF catalyst.

[0054] In step SO1,

[0055] The nickel salt is Ni(NO3)2·6H2O. The molybdenum salt is (NH4)6Mo7O 24 ·4H2O. The precipitant is thiourea.

[0056] The mixed solvent is a solvent in which ethylene glycol and deionized water are mixed in a volume ratio of 3:1.

[0057] In step SO2,

[0058] The foam iron substrate is pretreated in the following manner: the foam iron substrate is soaked in acetone for 10 minutes, taken out, and cleaned with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid for 2 minutes, taken out, and cleaned with deionized water to obtain a pretreated foam iron substrate.

[0059] The cleaning is achieved by ultrasound, the number of ultrasound is 3 times, and the duration of each ultrasound is 5 minutes. The hydrochloric acid is 0.1 mol / L hydrochloric acid.

[0060] The cleaning is achieved by ultrasound, the number of ultrasounds is 3 times, and the duration of each ultrasound is 5 minutes; the cleaning is carried out by ultrasound with deionized water and ethanol in sequence.

[0061] The drying step is drying at 60° C. for 12 h.

[0062] The Fe / NiMo@IF catalyst is a catalyst with a nanoscale heterogeneous structure, wherein the heterogeneous structure refers to NiMoO4 vertically grown on the surface of a foamed iron substrate in the form of an array of nanorods, the nanorods are interlaced to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

[0063] The structure of the prepared Fe / NiMo@IF catalyst was identified:

[0064] (1) Raman test: The Fe / NiMo@IF catalyst prepared in Example 1 was subjected to Raman test to obtain a Raman spectrum. Figure 1 shown; from Figure 1 It can be concluded that the catalyst prepared in Example 1 has the same peak shape and peak position as the NiMoO4@IF catalyst and the Fe3O4@IF catalyst, which further verifies the synthesis of the Fe / NiMo@IF catalyst. -1 The peak at 680.5cm is the Mo-O bond, while the peak at 680.5cm -1 The peak at is the Fe-O bond.

[0065] (2) SEM test: The Fe / NiMo@IF catalyst prepared in Example 1 was subjected to SEM scanning electron microscopy test. Figure 2 shown; from Figure 2 It can be seen that the Fe / NiMo@IF catalyst prepared in Example 1 is a catalyst with a nanoscale heterogeneous structure, in which NiMoO4 grows vertically on the surface of the foam iron substrate in the form of an array of nanorods, and the nanorods are intertwined to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

[0066] The performance of the prepared Fe / NiMo@IF catalyst was tested:

[0067] (1) The activity of the Fe / NiMo@IF catalyst in the two half reactions of hydrogen evolution (HER) and oxygen evolution (OER) in electrocatalytic water splitting was determined using a standard three-electrode system in 1M KOH solution. Specifically, linear sweep voltammetry (LSV), 1mVs -1 The polarization curves obtained at the scanning rate were used to compare the activity. The results are shown in Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 It can be seen that the Fe / NiMo@IF catalyst prepared in Example 1 only needs to apply 205 mV (such as Figure 3 In the oxygen evolution reaction, only 265 mV (as shown in Figure 4The overpotential shown in the figure can drive 100mA·cm -2 The current density is much higher than that of the Fe3O4@IF catalyst obtained without adding nickel source and molybdenum source (Comparative Example 1).

[0068] (2) The stability of the catalyst is also an important criterion for evaluating its performance. Figure 5 The relevant stability test results are shown. Figure 5 The data show that the Fe / NiMo@IF catalyst synthesized in Example 1 exhibits higher stability than the Fe3O4@IF catalyst obtained in Comparative Example 1. -2 When the oxygen evolution reaction was carried out under the conditions of , the activity of the catalyst did not decrease significantly.

[0069] Example 2

[0070] A method for preparing a Fe / NiMo@IF catalyst comprises the following steps:

[0071] SO1, add 0.732mmol nickel salt, 0.086mmol molybdenum salt and 6.57mmol precipitant into 20mL mixed solvent, stir and dissolve to obtain a mixed solution;

[0072] SO2, immerse the foamed iron vertically into the mixed solution in step SO1, and then react at 80°C for 18 hours. After the reaction is completed, cool naturally to room temperature to obtain a substrate with catalyst grown on it, clean the surface of the substrate with catalyst grown on it, and dry it to obtain Fe / NiMo@IF catalyst.

[0073] In step SO1,

[0074] The nickel salt is Ni(NO3)2·6H2O. The molybdenum salt is (NH4)6Mo7O 24 ·4H2O. The precipitant is thiourea.

[0075] The mixed solvent is a solvent in which ethylene glycol and deionized water are mixed in a volume ratio of 1:1.

[0076] In step SO2,

[0077] The foam iron substrate is pretreated in the following manner: the foam iron substrate is soaked in acetone for 10 minutes, taken out, and cleaned with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid for 2 minutes, taken out, and cleaned with deionized water to obtain the pretreated foam iron substrate.

[0078] The cleaning is achieved by ultrasound, the number of ultrasound is 2 times, and the duration of each ultrasound is 8 minutes. The hydrochloric acid is 0.1 mol / L hydrochloric acid.

[0079] The cleaning is achieved by ultrasound, the number of ultrasounds is 2 times, and the duration of each ultrasound is 4 minutes; the cleaning is carried out by ultrasound using deionized water and ethanol in sequence.

[0080] The drying step is drying at 60° C. for 12 h.

[0081] The Fe / NiMo@IF catalyst is a catalyst with a nanoscale heterogeneous structure, wherein the heterogeneous structure refers to NiMoO4 vertically grown on the surface of a foamed iron substrate in the form of an array of nanorods, the nanorods are interlaced to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

[0082] The performance test results of the prepared Fe / NiMo@IF catalyst are basically consistent with those in Example 1.

[0083] Example 3

[0084] A method for preparing a Fe / NiMo@IF catalyst comprises the following steps:

[0085] SO1, add 1.28mmol nickel salt, 0.151mmol molybdenum salt and 6.57mmol precipitant into 20mL mixed solvent, stir and dissolve to obtain a mixed solution;

[0086] SO2, immerse the foamed iron vertically into the mixed solution in step SO1, and then react at 180°C for 3 hours. After the reaction is completed, cool naturally to room temperature to obtain a substrate with catalyst grown on it, clean the surface of the substrate with catalyst grown on it, and dry it to obtain Fe / NiMo@IF catalyst.

[0087] In step SO1,

[0088] The nickel salt is Ni(NO3)2·6H2O. The molybdenum salt is (NH4)6Mo7O 24 ·4H2O. The precipitant is thiourea.

[0089] The mixed solvent is a solvent in which ethylene glycol and deionized water are mixed in a volume ratio of 2:5.

[0090] In step SO2,

[0091] The foam iron substrate is pretreated in the following manner: the foam iron substrate is soaked in acetone for 10 minutes, taken out, and cleaned with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid for 2 minutes, taken out, and cleaned with deionized water to obtain a pretreated foam iron substrate.

[0092] The cleaning is achieved by ultrasound, the number of ultrasound is 4 times, and the duration of each ultrasound is 5 minutes. The hydrochloric acid is 0.1 mol / L hydrochloric acid.

[0093] The cleaning is achieved by ultrasound, the number of ultrasounds is 4 times, and the duration of each ultrasound is 3 minutes; the cleaning is carried out by ultrasound using deionized water and ethanol in sequence.

[0094] The drying step is drying at 60° C. for 12 h.

[0095] The Fe / NiMo@IF catalyst is a catalyst with a nanoscale heterogeneous structure, wherein the heterogeneous structure refers to NiMoO4 vertically grown on the surface of a foamed iron substrate in the form of an array of nanorods, the nanorods are interlaced to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

[0096] The performance test results of the prepared Fe / NiMo@IF catalyst are basically consistent with those in Example 1.

[0097] Example 4

[0098] A method for preparing a Fe / NiMo@IF catalyst comprises the following steps:

[0099] SO1, add 1.647mmol nickel salt, 0.194mmol molybdenum salt and 6.57mmol precipitant into 20mL mixed solvent, stir and dissolve to obtain a mixed solution;

[0100] SO2, immerse the foamed iron vertically into the mixed solution in step SO1, and then react at 150°C for 6 hours. After the reaction is completed, cool naturally to room temperature to obtain a substrate with catalyst grown on it, clean the surface of the substrate with catalyst grown on it, and dry it to obtain Fe / NiMo@IF catalyst.

[0101] In step SO1,

[0102] The nickel salt is Ni(NO3)2·6H2O. The molybdenum salt is (NH4)6Mo7O 24 ·4H2O. The precipitant is thiourea.

[0103] The mixed solvent is ethylene glycol.

[0104] In step SO2,

[0105] The foam iron substrate is pretreated in the following manner: the foam iron substrate is soaked in acetone for 10 minutes, taken out, and cleaned with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid for 2 minutes, taken out, and cleaned with deionized water to obtain the pretreated foam iron substrate.

[0106] The cleaning is achieved by ultrasound, the number of ultrasound is 2 times, and the duration of each ultrasound is 10 minutes. The hydrochloric acid is 0.1 mol / L hydrochloric acid.

[0107] The cleaning is achieved by ultrasound, the number of ultrasound is 2 times, and the duration of each ultrasound is 5 minutes; the cleaning is carried out by ultrasound using deionized water and ethanol in sequence.

[0108] The drying step is drying at 60° C. for 12 h.

[0109] The Fe / NiMo@IF catalyst is a catalyst with a nanoscale heterogeneous structure, wherein the heterogeneous structure refers to NiMoO4 vertically grown on the surface of a foamed iron substrate in the form of an array of nanorods, the nanorods are interlaced to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

[0110] The performance test results of the prepared Fe / NiMo@IF catalyst are basically consistent with those in Example 1.

[0111] Comparative Example 1

[0112] A method for preparing a nano-particle structured Fe3O4@IF catalyst, wherein no nickel source and molybdenum source are added in the reaction, and the remaining raw materials, preparation method and performance tests are the same as those in Example 1, specifically comprising the following steps:

[0113] S01, add 6.57mmol of precipitant into 20mL of mixed solvent, stir and dissolve to obtain a mixed solution;

[0114] S02, immersing the foamed iron vertically into the mixed solution in step S01, and then reacting at 140°C for 6 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a substrate with catalyst grown on it, and the surface of the substrate with catalyst grown on it is cleaned and dried to obtain Fe3O4 / IF catalyst.

[0115] In step S01,

[0116] The precipitant is thiourea.

[0117] The mixed solvent is a solvent in which ethylene glycol and deionized water are mixed in a volume ratio of 3:1.

[0118] In step S02,

[0119] The foam iron substrate is pretreated in the following manner: the foam iron substrate is soaked in acetone for 10 minutes, taken out, and cleaned with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid for 2 minutes, taken out, and cleaned with deionized water to obtain the pretreated foam iron substrate.

[0120] The cleaning is achieved by ultrasound, the number of ultrasound is 3 times, and the duration of each ultrasound is 5 minutes. The hydrochloric acid is 0.1 mol / L hydrochloric acid.

[0121] The cleaning is achieved by ultrasound, the number of ultrasounds is 3 times, and the duration of each ultrasound is 5 minutes; the cleaning is carried out by ultrasound with deionized water and ethanol in sequence.

[0122] The drying step is drying at 60° C. for 12 h.

[0123] The Fe3O4@IF catalyst prepared in Comparative Example 1 was subjected to Raman testing to obtain a Raman spectrum. Figure 1 shown.

[0124] The electrocatalytic activity of the Fe3O4@IF catalyst prepared in Comparative Example 1 was tested at a current density of 100 mA cm -2 When the Fe3O4@IF catalyst prepared in Comparative Example 1 needs to apply an overpotential (η100) of 358 mV (e.g. Figure 3 ) and 451mV (as shown Figure 4 The performance is much lower than 205 mV and 265 mV of the Fe / NiMo@IF catalyst prepared in Example 1. It can be seen that the loading of Fe3O4 on NiMoO4 nanorods plays an important role in the electrochemical performance. In this way, two different reaction centers can be formed. The integration of the two different reaction centers can synergistically promote the water decomposition process to activate the bifunctional performance of the catalyst.

[0125] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a Fe / NiMo@IF catalyst, characterized in that: The steps include: SO1, adding nickel salt, molybdenum salt and precipitant into a mixed solvent, stirring until dissolved, to obtain a mixed solution; the molar ratio of the nickel salt, the molybdenum salt and the precipitant is (1.9-14.0): (1.3-2.3): 100; SO2, immerse the foamed iron substrate vertically in the mixed solution in step SO1, and then react at 80°C to 180°C for 3h to 18h. After the reaction is completed, naturally cool to room temperature to obtain a substrate with catalyst growth, clean the surface of the substrate, and dry it to obtain a Fe / NiMo@IF catalyst.

2. The method for preparing the Fe / NiMo@IF catalyst according to claim 1, characterized in that: In step SO1, the nickel salt is Ni(NO3)2·6H2O or Ni(CH3COO)2·4H2O.

3. The method for preparing the Fe / NiMo@IF catalyst according to claim 1, characterized in that: In step SO1, the molybdenum salt is (NH4)6Mo7O 24 4H2O; the precipitant is thiourea.

4. The method for preparing the Fe / NiMo@IF catalyst according to claim 1, characterized in that: In step SO1, the mixed solvent is a solvent in which ethylene glycol and deionized water are mixed in a volume ratio of (1-10):(1-10).

5. The method for preparing the Fe / NiMo@IF catalyst according to claim 1, characterized in that: In step SO2, the foam iron substrate is pretreated in the following manner: the foam iron substrate is soaked in acetone for 10 to 20 minutes, taken out, and washed with deionized water, and then the cleaned foam iron substrate is soaked in hydrochloric acid for 2 to 4 minutes, taken out, and washed with deionized water to obtain a pretreated foam iron substrate.

6. The method for preparing the Fe / NiMo@IF catalyst according to claim 5, characterized in that: The cleaning is achieved by ultrasound, the number of ultrasound is 2 to 4 times, and the time of each ultrasound is 5 minutes to 10 minutes; the hydrochloric acid is 0.1 mol / L hydrochloric acid.

7. The method for preparing the Fe / NiMo@IF catalyst according to claim 1, characterized in that: In step SO2, the cleaning is achieved by ultrasound, the number of ultrasounds is 2 to 4 times, and the duration of each ultrasound is 3 minutes to 5 minutes.

8. A Fe / NiMo@IF catalyst, characterized in that: The Fe / NiMo@IF catalyst is prepared by the preparation method described in any one of claims 1 to 7.

9. The Fe / NiMo@IF catalyst according to claim 8, characterized in that The Fe / NiMo@IF catalyst has a nanoscale heterogeneous structure, wherein the nanoscale heterogeneous structure refers to NiMoO4 vertically grown on the surface of a foamed iron substrate in the form of an array of nanorods, the nanorods are intertwined to form an open porous structure, and the surface and edges of the nanorods are loaded with Fe3O4 nanoparticles.

10. Use of the Fe / NiMo@IF catalyst according to claim 8 or claim 9, characterized in that: The Fe / NiMo@IF catalyst is applied to electrocatalytic water decomposition.